Widmo. Instrukcja obsługi (pierwsze uruchomienie) - Hoffmann, Krzysztof (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The paper’s aim is mainly propaedeutic: to provide the reader with the explanation of basic concepts of Derridean ‘Hauntology’. The first part of the article is based on three concurrent publications: first of all on the Polish translation of Specters of Marx by Jacques Derrida (2016) but also on Widmontologie nowoczesności by Jakub Momro (2014) and Widmontologia by Andrzej Marzec (2014). It focuses on the concepts of spectralization of being, spectralization of time and the “visor effect”. In the second part of the paper one can find applications of the hauntology to the contemporary cultural critical practice (e.g. to teletechnologies).